Migration and Education in Ghorahi-12, Dang: A Path to Rural Property Revitalization (Pragyaratna प्रज्ञारत्न, 2024)
Abstract:The study identified multiple dynamics of rural to urban migration and aims to analyze the impacts of migration on rural property. Mixed-methods approach is employed to achieve the defined goals. Quantitative data collection and analysis is given priority and then, qualitative data is collected and analyzed to offer comprehensive understanding. The study population of 1470 households comprise total migration from Hapur to Ghorahi has a significant impact on mode of rural property use. Among the migrants, (30.61%) have reported low supply of agricultural work force in rural areas. This results in either selling rural property or leaving it barren. As reported by 6.87 % of respondents, high connectivity among the relatives, friends and local government is well entertained due to migration. A high majority of the migrants, 61.43%, expressed that quality education remained the reason behind migration from Hapur to Ghorahi but the property in Hapur remained neglected due to distance management. Not the expansion of the urban areas, but the transformation of rural to urban accelerates overall development. Education, in this context, can be the comprehensive tool for rural urbanization with strong socio-economic foundation.